MINERAL COMPOSITION OF WILD RELATIVES AND INTROGRESSIVE FORMS IN WHEAT SELECTION - T. V. Savin; A. I. Abugaliyeva; I. Cakmak; K. Kozhakhmetov (Вавиловский журнал генетики и селекции, 2018)
The study of seed mineral composition of wheat and its wild relatives revealed higher content of all elements in Aegilops ovata and Ae. triuncialis, as well as an overall increased background in relatives compared to modern varieties of Triticum aestivum (standards). By content of macro- and microelements, synthetic forms of wheat occupy an intermediate position between wild relatives and modern varieties. Transitional forms with the level of mineral composition typical of wild forms (Zhetysu×T. militinae; Zhetysu×T. kiharae; Bezostaya 1×Ae. cylindrica) have been identified. All genotypes have been differentiated into 3 clusters. The first consists predominantly of introgressive forms, Ae. triaristata and the Komsomolskaya 1 variety, which has wild forms in its origin. The second cluster includes mainly varieties (parental forms), T. timopheevii and the introgressive form (Steklovidnaya 24×T. militinae). The third cluster consists largely of T. militinae, T. kiharae, Ae. cylindrica species and introgressive forms originated from them: Zhetysu×T. militinae and Bezostaya 1× Ae. cylindrica. Such division allows us to classify genotypes according to the level of metabolism: wild relatives (3rd cluster), varieties (2nd cluster) and an intermediate group – introgressive forms (1st cluster). In general, inclusion of cultural forms (backcrossing with varieties) to crosses with introgressive forms is usually accompanied by a decrease in the total metabolic level, but it varies in cultivars and wild species characterized by polymorphism. Sources of high content of elements have been revealed: wild relatives and introgressive forms, some of which are donors. According to the results of topcross breeding with testers – commercial common wheat varieties Steklovidnaya 24, Almali, Zhetysu – inheritance of this trait by progenies in F2–F3 generations has been revealed in two constant lines: (Bezostaya 1×Ae. cylindrica)×T. kiharae and Zhetysu×T. kiharae.